2016
DOI: 10.1007/s10461-016-1295-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Heterosexual Anal Intercourse Among Men and Women, 20 U.S. Cities

Abstract: Heterosexual anal intercourse (HAI) is not an uncommon behavior and it confers a higher risk of HIV transmission than vaginal intercourse. We examined data from heterosexuals recruited in 20 US cities for the 2013 National HIV Behavioral Surveillance system. We assessed correlates of reporting HAI in the previous year. Then, among people reporting HAI in the past year, we assessed what event-level factors are associated with having HAI at last sex. Thirty percent of women and 35% of men reported HAI in the pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 26 publications
6
36
0
Order By: Relevance
“…These associations with longitudinal AI practice are similar to associations identified in cross-sectional studies, where AI practice has been reported as more common among Hispanic than black women, 23e28 among white compared to black women, 3,29,30 among women who have sex with both men and women, 3,25,31,32 among survivors of sexual 23,33e38 and physical violence, 33,39e41 and among women with multiple male sex partners. 3,8,42,43 Overall, AI was reported at a tenth of visits at which a male sex partner was reported, and by 12% of women within the first year of follow-up. This is similar to the 11% of women in a nationally representative 2015 survey who reported AI in the past year, 44 but less common than the 30% reporting AI over the same recall period in the National HIV Behavioral Surveillance System (NHBS-HET), which sampled sexually active women of low The model is also adjusted for recruitment wave.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These associations with longitudinal AI practice are similar to associations identified in cross-sectional studies, where AI practice has been reported as more common among Hispanic than black women, 23e28 among white compared to black women, 3,29,30 among women who have sex with both men and women, 3,25,31,32 among survivors of sexual 23,33e38 and physical violence, 33,39e41 and among women with multiple male sex partners. 3,8,42,43 Overall, AI was reported at a tenth of visits at which a male sex partner was reported, and by 12% of women within the first year of follow-up. This is similar to the 11% of women in a nationally representative 2015 survey who reported AI in the past year, 44 but less common than the 30% reporting AI over the same recall period in the National HIV Behavioral Surveillance System (NHBS-HET), which sampled sexually active women of low The model is also adjusted for recruitment wave.…”
Section: Discussionsupporting
confidence: 80%
“…1 Cross-sectional studies consistently suggest that AI is commonly practiced among US cisgender women (referred to here as women), with a systematic review on AI among young people estimating that 25% (95% confidence interval [CI]: 20e29%) of sexually active young women and girls (aged <25 years) in North America had ever practiced AI. 2 A survey of sexually active women living in 20 US cities with high HIV prevalence found that 30% reported AI within the past year, 3 and a mathematical modeling study based on the same survey estimated that 4 in 10 new HIV infections in that population may be attributed to condomless AI. 4 While we have a fair understanding through cross-sectional studies of how commonly women may practice AI, there has, to our knowledge, been no longitudinal examination of women's AI practice over the life course.…”
Section: Introductionmentioning
confidence: 99%
“…Irrespective of childhood traumatic experiences, engagement in anal intercourse was reported by a sizeable percentage of the young adult women in our study, mirroring estimates from other nationally representative U.S. samples, in which approximately one-third of women reported having had anal intercourse. 55,56 Our findings corroborate earlier studies regarding higher RAI prevalence among white women and those with higher levels of education. Specifically, in the 2013 National HIV Behavioral Surveillance survey, approximately 30% of black women reported anal intercourse compared with 40% of white women; 55 and in the 2006-2008 National Survey of Family Growth, 32% of women with less than a high school education reported RAI, whereas the prevalence was 39% among women with higher education levels.…”
Section: Discussionsupporting
confidence: 91%
“…Irrespective of childhood traumatic experiences, engagement in anal intercourse was reported by a sizeable percentage of the young adult women in our study, mirroring estimates from other nationally representative U.S. samples, in which approximately one‐third of women reported having had anal intercourse . Our findings corroborate earlier studies regarding higher RAI prevalence among white women and those with higher levels of education.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation